School - Edward, S. Ebert II (Thomson Wadsworth, 2007)
Learn what it takes to be an effective professional teacher with SCHOOL: AN INTRODUCTION TO EDUCATION. Based on the ten standards developed by the INTASC (Interstate New Teacher Assessment and Support Consortium), teachers are expected to be reflective, knowledgeable, highly skilled, and creative professionals who are lifelong learners. With this text, authors Edward Ebert and Richard Culyer have developed a compelling and timely approach that gives you a thorough overview of what it means to be a successful teacher. You'll read first-person accounts and get helpful strategies and tips from prominent educators--as well as in-service teachers--that give you realistic insight into what it means to be an educator in today's rapidly changing society. SCHOOL: AN INTRODUCTION TO EDUCATION is a timely text that will empower you as a pre-professional and, ultimately, as an instructional leader